2015
DOI: 10.5367/te.2014.0402
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Nowcasting Tourist Arrivals in Barbados – Just Google it!

Abstract: This paper uses support vector regressions (SVRs) and Google search data to test whether observing Internet habits can provide insights into trends in tourist arrivals in Barbados. The empirical evidence suggests that Google Trends data may be used to pick up changing patterns and trends in tourist arrivals from the UK and Canada. In the case of the USA, the authors find no evidence to suggest that Google data add any significant information to what can be ‘learned’ from an autoregressive SVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Volchek et al (2019) compare mixed-frequency data sampling with ANN models and claim that higher frequency search data enhance the performance of models used to predict tourism demand. In contrast, Jackman and Naitram (2015) find no evidence suggesting that Google Trends data add any significant information to the models. The authors use support vector regressions and Google search data to test whether Google Trends can help predict tourist arrivals in Barbados.…”
Section: Literature Reviewmentioning
confidence: 69%
“…Volchek et al (2019) compare mixed-frequency data sampling with ANN models and claim that higher frequency search data enhance the performance of models used to predict tourism demand. In contrast, Jackman and Naitram (2015) find no evidence suggesting that Google Trends data add any significant information to the models. The authors use support vector regressions and Google search data to test whether Google Trends can help predict tourist arrivals in Barbados.…”
Section: Literature Reviewmentioning
confidence: 69%
“…In other words, the fit between the estimation model and the prediction model is good. Next, the forecasting ability was tested based on two forecasting accuracy criteria: RMSE and MAPE (Jackman & Naitram, ; Li et al, ). Table shows the predictive accuracy evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al () empirically tested a framework for predicting tourist numbers to Beijing by incorporating search‐trend data and found similar results. Jackman and Naitram () explored support vector regressions and Google search data to test whether observing people's Internet habits could provide insights into trends in tourist arrivals to Barbados. Their findings revealed that Google Trends data could be used to identify changing patterns and trends in tourist arrivals from the UK and Canada.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Support Vector Regressions were used in Jackman and Naitram (2016) to determine if Google search data can act as an indicator for trends in tourist arrivals in Barbados. The authors find that whilst Google Trends data can pick up significant information pertaining to tourist arrivals from UK and Canada there is no evidence in terms of tourist arrivals from US.…”
Section: Literature Reviewmentioning
confidence: 99%